Analisis Kepuasan Petani Terhadap Atribut Benih Kentang (G2) Industri di Kabupaten Garut - Wibawa, Diky Indra; Noor, Trisna Insan; Rachmadi, Meddy; Deliana, Yosini; Tridakusumah, Achmad Choibar; Renaldy, Eddy (Universitas Galuh, 2024)
Satisfaction is a product that is preferred to fulfill its desires. Potatoes are horticultural crops that have high carbohydrate content, adaptive business segments, clear markets, non-perishability, longer shelf life, and high economic value. Farmer satisfaction in assessing various attributes of seed potatoes is assessed from the fulfillment of expectations or expectations that are met, good performance, and perceived benefits. The purpose of this study is to measure farmers' satisfaction with industrial seed potatoes in Garut Regency. This study used a quantitative method with a descriptive analysis approach involving 100 respondents using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) analysis tools. The research was conducted in two districts in Garut Regency. The results of the study show that the level of satisfaction of potato farmers is at a satisfied level, where the attributes of industrial potato seeds included in Quadrant I are pest-free potato seeds and ease of obtaining them, seed morphology that has resistance to pests, seed production calculated from productivity and the number of tubers, market convenience, tuber selling prices, and services in assisting the production process. While the attributes of industrial potato seeds included in Quadrant II are price and quality assurance of distributed seeds. Then, located in Quadrant III are the purchase price of seeds and the timeliness of delivery. The need for both farmers and the government to intensify the use of certified superior potato seeds in order to produce potato production and productivity in accordance with market demand.